A Meta-Analysis Study of Principal Leadership and Teacher Job Satisfaction - Juhji Juhji; Ilzamudin Ma’mur; Enung Nugraha; Arisal Nurhadi; Nafan Tarihoran (STAI Hubbulwathan Duri, 2022)
This paper aims to analyze the relationship between principal leadership and teacher job satisfaction in recent years. This research uses a systematic review and meta-analysis using JASP 0.14.1.0 software. The search for relevant articles through the Garuda, Eric, and Google Scholar databases with the keywords transformational leadership of school principals and job satisfaction was carried out by the research team. Based on the search results, Garuda found eight articles, Eric found 708 articles, and Google Scholar found 2,820 articles. Furthermore, based on the criteria: leadership, principal leadership, transformational leadership, and teacher job satisfaction, ten articles were selected. The data taken from the selected articles is the number of samples and the r-value in each article. After that, the effect size is calculated. A significant correlation between principals' transformational leadership and teacher job satisfaction was found based on the results of the meta-analysis. The effect size value resulting from the relationship between the two variables is categorized as moderate at the 95 percent confidence level. The effect size value is 0.50, in the interval 0.39 to 0.61. Research analysis in this study has stated the consistency of research and has strengthened existing theories. The results of the study recommend that further research be conducted on madrasah principals and madrasah teachers.